Use of Tranexamic Acid to Reduce PostOperative Bleeding in Orthopaedic Oncology - Andreani, Lorenzo; Del Chiaro, Andrea; Ipponi, Edoardo; Di Sacco, Federico; Caterino, Martina; Capanna, Rodolfo (Acta medica Lituanica, 2022)
Background: Orthopaedic oncology often causes major blood losses that may put at risk patients’ hemodynamic balance and their overall clinical stability. To this date, transfusion therapy still represents the pivotal treatment to counterbalance the reduction in hemoglobin levels which occur after surgery. Although effective, transfusions are expensive and inevitably associated with a number of complications and therefore other solutions, such as procoagulative drugs, could play an important role to prevent massive blood losses. Material and methods: We reviewed the clinical intercourse of 37 patients who underwent major bone resection due to malignant tumors of the lower limb. Cases were divided in two different groups: group G1 consisting of 12 patients treated intraoperatively with tranexamic acid and group G2 which was made of 25 controls. Results: On average, patients treated with tranexamic acid (G1) required transfusion of 3.9 concentrated blood cells units during surgery and 0.9 units during the postoperative course. Other patients (G2), for their part, required on average 3.1 units intraoperatively and 2.1 units postoperatively. No significant difference was found in intraoperative transfusion rate (p=0.402). Instead, postoperative transfusions were significantly less frequent for patients treated with tranexamic acid (p=0.023). None of the 12 patients treated with tranexamic acid had evidence of Deep Vein Thrombosis. Conclusion: Our outcomes indicate that the use of TXA was effective in reducing blood losses also for major surgical interventions in orthopedic oncology.